Ace school

with brainly

  • Get help from millions of students
  • Learn from experts with step-by-step explanations
  • Level-up by helping others

A community for students.

would the answer of (a − b)(a − b) be a^2 - ab^2 - b^2

Mathematics
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

FOIL First: a*a = a^2 Outside = -ab Inside = -ab Last = -b(-b) = +b^2 What do we do with the -ab and the -ab?
Tkink -x + -x = -2x
I know to combine itt

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

@chungerforever remember when we had \(5x+5x=10x\)? don't change the exponents here either
\(-ab-ab=?\)
oh minus! so just ab?
\(-10-10=?\)
oh I understand, so the answer is just a^2 - b^2?
hold the phone, careful arithmetic \(-10-10=?\)
hint, it is not 0
I'm sorry I have no idea, I'm not good at algebra ):
-10?
don't fret, we will work it out, but i was asking an arithmetic question \(-10-10=-20\)
\(-100-100=?\)
-200?
yes that is it !
\(-7-7=?\)
-14
ok good now we can move on to variables
\[-10-10=-20\] \[-100-100=-200\] \[-7-7=-14\] \[-12-12=-24\] and so on how about \[-x-x\]? well this must be the same as the others, namely \[-x-x=-2x\]
so -2ab?
notice that the exponent does not change spend $20, spend another $20 you have spent \(2\times 20=40\) yes you have it !
so "final answer" for \((a-b)(a-b)\) is ??
a^2 - 2ab - b^2?
yes that is it!
thank you so much! and sorry I was taking a while to reply. But thanks again I appreciate it (:
yw good work, hope you are understanding a bit more about combining like terms

Not the answer you are looking for?

Search for more explanations.

Ask your own question